2020
DOI: 10.3390/ijms21249679
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of PLLA, PTFE and PVDF with Extreme Ultraviolet (EUV) to Enhance Cell Adhesion

Abstract: Recently, extreme ultraviolet (EUV) radiation has been increasingly used to modify polymers. Properties such as the extremely short absorption lengths in polymers and the very strong interaction of EUV photons with materials may play a key role in achieving new biomaterials. The purpose of the study was to examine the impact of EUV radiation on cell adhesion to the surface of modified polymers that are widely used in medicine: poly(tetrafluoroethylene) (PTFE), poly (vinylidene fluoride) (PVDF), and poly-L-(lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…Also, the presence of that group was not demonstrated in materials modified in the presence of nitrogen gas. Similar results were obtained in our previous studies on modifying other polymers (PTFE, PLLA, PVDF) [39]. In the study, we also observed lower WCA values for surfaces modified in an oxygen atmosphere compared to those modified in a nitrogen atmosphere.…”
Section: Wettabilitysupporting
confidence: 91%
See 1 more Smart Citation
“…Also, the presence of that group was not demonstrated in materials modified in the presence of nitrogen gas. Similar results were obtained in our previous studies on modifying other polymers (PTFE, PLLA, PVDF) [39]. In the study, we also observed lower WCA values for surfaces modified in an oxygen atmosphere compared to those modified in a nitrogen atmosphere.…”
Section: Wettabilitysupporting
confidence: 91%
“…It is worth noting that the C-OH groups were not present in Also, the presence of that group was not demonstrated in materials ence of nitrogen gas. Similar results were obtained in our previous s other polymers (PTFE, PLLA, PVDF) [39]. In the study, we also o In our study, the modification process conducted in the presence of oxygen resulted in the formation of hydrophilic C-OH groups (Table 1).…”
Section: Wettabilitysupporting
confidence: 89%
“…Several studies report PLLA activity related to cell adhesion [ 59 , 60 ]. In addition to cell adhesion proofing, Yanagida et al [ 61 ] for instance, verified the response to PLLA tissue coated with hydroxyapatite nanocrystal (HAp).…”
Section: Resultsmentioning
confidence: 99%
“…The use of liquid bioactive material improves implant wettability and influences the early stages of osteointegration. However, the reactivity of liquid bioactive surfaces is dependent on their hydrophilic competency, salt composition and concertation, electrodynamic charge, lack of solid components, and proteins, factors that may influence viscosity, stiffness, and roughness [ 29 , 48 , 49 ]. Anitua et al’s innovative work using titanium implants pre-treated with liquid PRGF proved that the implants accelerate bone regeneration, reduce post-extraction defects, and thus, shorten the time between tooth extraction and implant insertion [ 34 , 35 , 36 , 38 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%